9+3(2u-3)=-3(6u-6)+8u

Simple and best practice solution for 9+3(2u-3)=-3(6u-6)+8u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3(2u-3)=-3(6u-6)+8u equation:


Simplifying
9 + 3(2u + -3) = -3(6u + -6) + 8u

Reorder the terms:
9 + 3(-3 + 2u) = -3(6u + -6) + 8u
9 + (-3 * 3 + 2u * 3) = -3(6u + -6) + 8u
9 + (-9 + 6u) = -3(6u + -6) + 8u

Combine like terms: 9 + -9 = 0
0 + 6u = -3(6u + -6) + 8u
6u = -3(6u + -6) + 8u

Reorder the terms:
6u = -3(-6 + 6u) + 8u
6u = (-6 * -3 + 6u * -3) + 8u
6u = (18 + -18u) + 8u

Combine like terms: -18u + 8u = -10u
6u = 18 + -10u

Solving
6u = 18 + -10u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '10u' to each side of the equation.
6u + 10u = 18 + -10u + 10u

Combine like terms: 6u + 10u = 16u
16u = 18 + -10u + 10u

Combine like terms: -10u + 10u = 0
16u = 18 + 0
16u = 18

Divide each side by '16'.
u = 1.125

Simplifying
u = 1.125

See similar equations:

| (x+8)(x+6)=32 | | 8(9b+4)=-32 | | 2-(2c+3)=-3(3c-4) | | 2/3b9 | | (3x+5)(9x-5)=0 | | 2x^2+3x-2x-3=18 | | 11.5(4+X)= | | 5z+5=6-4z+17 | | 6=a+9 | | sec*x-secx-2=0 | | 2(2y+1)=(5y-2) | | 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 | | 80x^2-720=0 | | 8=3x+bx | | 12z+4x=-7 | | 27q-9=180 |

Equations solver categories